2016
DOI: 10.1016/j.parco.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

An approach for code generation in the Sparse Polyhedral Framework

Abstract: Applications that manipulate sparse data structures contain memory reference patterns that are unknown at compile time due to indirect accesses such as A [B[i]]. To exploit parallelism and improve locality in such applications, prior work has developed a number of run-time reordering transformations (RTRTs). This paper presents the Sparse Polyhedral Framework (SPF) for specifying RTRTs and compositions thereof and algorithms for automatically generating efficient inspector and executor code to implement such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Tiling of consecutive SpMVs on unstructured grids is much harder. However, the sparse polyhedral framework (SPF) [35,25], an extension of full sparse tiling [34], attempts to generalize polyhedral loop transformations to codes with indirect memory references, as used in general SpMVs. While the standard polyhedral framework is restricted to compiling c 2015 U.S. Government Downloaded 07/18/15 to 130.132.123.28.…”
Section: Discussionmentioning
confidence: 99%
“…Tiling of consecutive SpMVs on unstructured grids is much harder. However, the sparse polyhedral framework (SPF) [35,25], an extension of full sparse tiling [34], attempts to generalize polyhedral loop transformations to codes with indirect memory references, as used in general SpMVs. While the standard polyhedral framework is restricted to compiling c 2015 U.S. Government Downloaded 07/18/15 to 130.132.123.28.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, these approaches focus on dense loops over dense arrays, so are not applicable to our domain. There has been work done in the past to generalize the loop-based model to handle non-affine loop bounds and subscripts using symbolic expressions [23,34], and to handle sparse matrices and arrays [30][31][32]35], but these approaches still only target loops, and hence do not generalize to the recursive constructs we consider. To break down the transformations a little more concretely, first, the method outer was strip mined (Section 5.3.4) to break it into two loops, outer1 (at line 1) and outer2 (at line 16); outer2 performs groups of 4 iterations from outer1.…”
Section: Other Related Workmentioning
confidence: 99%
“…Strout et al [56] first demonstrated the feasibility of automatically generating inspectors and composing separately specified inspectors using the sparse polyhedral framework; the inspector-executor generator prototype composed inspectors by representing them using a data structure called an inspector dependence graph. Subsequently, Venkat et al [29], [57] developed automatically-generated inspectors for nonaffine transformations and for data transformations to reorganize sparse matrices into different representations that exploit the structure of their nonzeros.…”
Section: Polyhedral Compiler Optimization Of Sparse Matricesmentioning
confidence: 99%